PENGARUH KUALITAS PENGAWASAN INTERNAL DAN PEMAHAMAN AUDIT INTERNAL TERHADAP AKUNTABILITAS KEUANGAN (Studi Kasus KSP Kopdit Pintu Air) - Petrus Satu, Emanuel; Pati Sanga, Konstantinus; Libu Lamawitak, Paulus (Jurnal Projemen UNIPA, 2025)
This study aimed to examine the effect of internal supervision quality and internal audit understanding on financial accountability (a case study of KSP Kopdit Pintu Air). A quantitative rescarch method with an associative approach was employed, involving 50 employees of KSP Kopdit Pintu Air as respondents. Data were collected through questionnaires and analyzed using validity and reliability tests, descriptive statistics, classical assumption tests, multiple linear regression analysis, as well as partial (t-test) and simultaneous (F-test) hypothesis testing. The findings revealed that (1) internal supervision quality had a positive but insignificant effect on financial accountability, (2) internal audi understanding had a positive but insignificant effect on financial accountability, and (3) internal supervision quality and internal audit understanding jointly had no significant effect on financial accountability. The Adjusted R³ value of 0.010 indicated that the independent variables explained only 1% of the variance in financial accountability, while the remaining 99% was influenced by other factors outside the scope of this research model.